Protoype Sistem Buka Tutup Pintu Air Otomatis pada Persawahan Berbasis Arduino Uno - Pramudita, Dimas; , Dr. Agus Ulinuha, ST. MT. Ph.D (2017)
Improvements in managing the farm is needed at this time. As the number of occurrences of crop failure due to the rainy season that caused flooding in rice fields. Lack of supervision of the irrigation system to make the water flow when heavy rainfall causes rice plants destroyed by the water current. This is required by the regulator of immigration channels to prevent crop failure and flooding. Along with this problem, invented prototype system based automated sluice Arduino. This prototype has a second function of the first set when the doors of water in reservoirs operate with reference height of water using ultrasonic sensors. The sensor signal into Arduino for Arduino ordered proses. The output signal from arduino ordered the relay to be active and work solenoid to open or close the drains. Functions to 2 to manage reservoir which has a door leading to the water drain rice fields. Sluice works by setting a time that can be set as desired. Prototype sluice gates on irrigation driven by 12V DC motor and lock the door when open water using servo motors. With the second operation this function, may facilitate setting the water level in reservoirs and irrigation channel management area of rice fields.